On Flora Saunt being vain: aspectuality and the social construction of identity in Henry James's 'Glasses' (1896). Issue 7 (9th August 2019) - Álvarez-Amorós, José A.
ABSTRACT: Using notions such as aspectuality, metarepresentation, extended cognition, and distributed identity, which were first developed by cognitive psychology and philosophy of mind and later adapted to the study of fictional consciousness by cognitive narratology, this paper explores the social construction of Flora Saunt's identity in Henry James's 'Glasses' (1896). This short story is a fine specimen of a group of first-person Jamesian narratives which could be summarily characterised as tales of absent or effaced protagonists for the simple reason that their alleged central figures are seldom, if ever, directly available to the reader and mostly exist as sets of consensual or conflicted images lodged in the minds of other inhabitants of the storyworld. In the specific case of 'Glasses', for instance, an analysis of its cognitive make-up provides sufficient evidence to conclude that the construction of Flora as a vain, deceitful woman is heavily contingent on the gender peculiarities of the sources that represent and metarepresent her mind.